Internet-delivered cognitive behaviour therapy for depression in people with diabetes: study protocol for a randomised controlled trial. Issue 1 (30th November 2015) - Robins, Lisa; Newby, Jill; Wilhelm, Kay; Smith, Jessica; Fletcher, Therese; Ma, Trevor; Finch, Adam; Campbell, Lesley; Andrews, Gavin
Abstract : Introduction: Depression substantially contributes to the personal burden and healthcare costs of living with diabetes mellitus (DM). Comorbid depression and DM are associated with poorer quality of life, poorer self-management and glycemic control, increased risk for DM complications and higher mortality rates, and higher health service utilization. Depression remains under-recognized and undertreated in people with DM, which may, in part, result from barriers associated with accessing face-to-face treatment. This study will examine the efficacy of an internet-based cognitive behaviour therapy programme for major depressive disorder (iCBT-MDD) in people with DM. Methods and analysis: A CONSORT 2010 compliant, registered randomised controlled trial of the intervention (iCBT-MDD) versus a treatment as usual control group will be conducted. The study will include 100 adults aged 18 years and over with a diagnosis of type 1 or type 2 DM and self-reported symptoms that satisfy MDD which will enable us to detect a statistically significant difference with a group effect size of 0.6 at a power of 80% and significance level of p=0.05. Participants will be randomised to receive the iCBT-MDD programme immediately, or to wait 10 weeks before accessing the programme. Primary outcomes will be self-reported depression severity, DM-related distress, and glycemic control (glycosylated hemoglobin). Secondary outcomes will be general distress and disability, generalized anxiety, lifestyle behaviours, somatization, eating habits, alcohol use, and acceptability of the iCBT programme to participants, and practicality for clinicians. Data will be analyzed with linear mixed models for each outcome measure. Ethics and dissemination: The Human Research Ethics Committee of St Vincent's Hospital Australia have given ethics approval (HREC/13/SVH/291). Results will be disseminated via peer-reviewed publication and social media channels of Australian Diabetes Consumer Representative Bodies. Trial registration number: The trial is registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12613001198718).